The 1989 revolutions in Central and Eastern Europe : from communism to pluralism - McDermott, Kevin, 1957-; Stibbe, Matthew (Manchester University Press ; Distributed in the United States exclusively by Palgrave Macmillan, 2013)
"This important book reassesses a defining historical, political and ideological moment in contemporary history: the 1989 revolutions in central and eastern Europe. Adopting a multi-disciplinary approach, the authors reconsider such crucial themes as the broader historical significance of the 1989 events, the complex interaction between external and internal factors in the origins and outcomes of the revolutions, the impact of the 'Gorbachev phenomenon', the West and the end of the Cold War, the political and socio-economic determinants of the revolutionary processes in Poland, Hungary, the German Democratic Republic, Czechoslovakia, Romania and Bulgaria, and the competing academic, cultural and ideological perceptions of the year 1989 as communism gave way to post-communist pluralism in the 1990s and beyond. Concluding that the contentious term 'revolution' is indeed apt for the momentous developments in eastern Europe in 1989, this book will be essential reading for undergraduates, postgraduates and specialists alike."--Publisher's description